PENERAPAN COST-VOLUME-PROFIT DALAM PENGAMBILAN KEPUTUSAN UNTUK PERENCANAAN LABA PADA HOTEL FAJAR ROON MANOKWARI - Antameng, Desy Pratiwi; Lambey, Linda; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2017)
Profit becomes one of the indicators to assess the performance of a company, to be able to achieve the desired profit by a company needs a good profit planning. The existence of profit planning enables companies to control costs even to identify problems that exist. The purpose of this study is to analyze the mechanism of profit planning at Hotel Fajar Roon Manokwari and how to apply profit planning at Hotel Fajar Roon Manokwari by using cost-volume-profit analysis method. The research method used is descriptive method. The result of this research is known that Fajar Roon Manokwari Hotel in determining its profit target only use occupation method (occupancy rate), Then profit planning that use occupation is felt less effective because the plan only give the level of presentation of planned profit without giving clear direction how Sales to be achieved next year, this means the hotel only gives the level of profit alone without providing sales targets next year that must be pursued to achieve the desired profit. This is evident from the profit realized with the target hotel profit using occupation is always not the same. Therefore, Hotel Fajar Roon Manokwari in determining profit planning should use cost-volume-profit analysis method because it can set its profit target by looking at changes of several factors such as cost, sales volume, and selling price, besides using cost-volume Profit companies can also know the sales revenue that a company should target to get the desired profit. Keywords : analysis of cost-volume-profit, profit planning.